Prudential Issues in Less Diversified Economies - Narain, Aditya (IMF Working Papers; Working Paper ;, 2003)
This paper examines the prudential issues associated with credit concentration in less diversified economies (LDEs), which are identified as countries where one or two sectors represent a large share of exports. In preparing this analysis, the characteristics of their financial and banking systems and their interactions with the real sector are studied. The paper also examines the limitations on portfolio diversification confronting banks in these countries, both from the viewpoint of the real sector and of the financial system. The paper finds that banks in LDEs, particularly in low-income countries, appear to face higher risk than their peers in more diversified economies and makes suggestions for policy options and regulatory practices which could be encouraged in such systems.